The art and science of mentoring : a Festschrift in honor of Dr. Frances Kochan - Reames, Ellen H.; Searby, Linda; Kochan, Frances K. (Emerald Publishing Limited : Information Age Publishing, Inc., 2021)
"The Art and Science of Mentoring is a collection of chapters and vignettes that honors one of the leading experts of mentoring, Fran Kochan. Her amazing role of being able to blend theory and practice in regards to mentoring is captured in these pages. As one protégé said, "She practices what she preaches." The volume is divided into an introduction, Part II, which explores important concepts and ideas in regards to mentoring and then Part III which are essays from individuals whom Fran Kochan mentored throughout her life. In closing, Fran Kochan lives and breathes her words. Even today, she continues to work with scholars, practitioners and others she meets. She offers a guiding hand, she uplifts and she supports all that she meets. Please enjoy this volume of highlights of research from top mentoring experts who are peers of Dr. Kochan, as well as the tributes from a sampling of individuals she has mentored to successful careers. You will be inspired to learn how Dr. Fran Kochan masters both the art and science of mentoring. We honor her in this book as scholar, mentor, and friend. How do you envision the book's cover? What image(s) would you envision? We would like Vincent Van Gogh's Stary Night on the front cover. Fran is an avid lover and supporter of the visual arts and travels with friends and families to museums throughout the United States and the world. It is a tribute to her. Van Gogh was also a very spiritual being as is Fran Kochan and his work represents the constellations. This is a well-known mentoring conceptual framework: "mentoring constellations""--